Differentiable Net-Moving and Local Congestion Mitigation for Routability-Driven Global Placement - Li, Wenchao; Wu, Hongxi; Liu, Duanxiang; Li, Xingquan; Zhu, Wenxing (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Routability-driven global placement is a major challenge in modern VLSI physical design, for which mitigating routing congestion is a critical approach. Cell inflation can effectively address local routing congestion and is widely adopted, but with the issue of over-inflating or moving cells back into congested areas. Minimizing the congestion within a net bounding box is effective for alleviating global routing congestion, but the bounding box may be too large and contain congestion not contributed by the net. To address the first issue, we propose a momentum-based cell inflation technique that considers historical inflation ratios for mitigating local routing congestion. Then, we construct a differentiable global congestion function, developed from Poisson's equation, and introduce virtual standard cells onto two-pin nets to accurately guide net movements for mitigating global routing congestion. Furthermore, to improve pin accessibility, we adjust placement density around power and ground rails according to the routing congestion in global placement. The proposed techniques are integrated into an electrostatic-based global placement framework. Experiments on the ISPD 2015 contest benchmarks show that our framework achieves better routability results, with an average of 40% DRVs reduction and comparable wirelength and via count, compared to the leading routability-driven placer.